RELEVANSI NILAI AKUNTANSI AKRUAL VERSUS KAS - Zuhrotul Isnaini; Rahmi Sri Ramadhani; Muhammad Ali Fikri (Jurusan Akuntansi Fakultas Ekonomi Dan Bisnis Universitas Mataram, 2020)
Value relevance specifically explains the relationship between the dependent variable, which is based on the price of a security, and the independent variable of accounting information. There are two common measurement methods used by investors to determine the value of accounting information, namely the profit and loss approach and the balance sheet approach which are both accrual-based. This study uses a qualitative approach, which employed respondents of lecturers of Capital Market subjects, Accountants/consultants, and members of the IAI of NTB Region. The results of the study generally states that the accrual approach has a small impact on changes in stock prices and different from the cash flow.